A Deep Redshift Survey of the Perseus Cluster (A426): Spatial Distribution and Kinematics of Galaxies - Kang, Wooseok; Hwang, Ho Seong; Song, Hyunmi; Park, Changbom; Hwang, Narae; Park, Byeong-Gon (The Astrophysical journal. Supplement series, 2024)
We study the global kinematics of the Perseus galaxy cluster (A426) at redshift z = 0.017 using a large sample of galaxies from our new MMT/Hectospec spectroscopic observation for this cluster. The sample includes 1447 galaxies with measured redshifts within 60′ from the cluster center (1148 from this MMT/Hectospec program and 299 from the literature). The resulting spectroscopic completeness is 67% at r -band apparent magnitude r Petro,0 ≤ 18.0 within 60′ from the cluster center. To identify cluster member galaxies in this sample, we develop a new open-source Python package, CausticSNUpy. This code implements the algorithm of the caustic technique and yields 418 member galaxies within 60′ of the cluster. We study the cluster using this sample of member galaxies. The cluster shows no significant signal of global rotation. A statistical test shows that the cluster does not have a noticeable substructure within 30′. We find two central regions where the X-ray-emitting intracluster medium and galaxies show significant velocity differences (>7 σ ). On a large scale, however, the overall morphology and kinematics between the intracluster medium and galaxies agree well. Our results suggest that the Perseus cluster is a relaxed system and has not experienced a recent merger.